Pemanfaatan Fermentasi Ampas Kelapa Sebagai Pakan Tambahan terhadap Peningkatan Performa Kambing Boerka - Fransiskus Jeski Neonbeni; Edelnia Kristina Bere; Reni Ratni Dapawole (Institut Nalanda, 2026)
This study aimed to determine the effect of fcoconut meal supplementation on the performance of Boerka goats, including average daily gain (ADG), feed intake, and feed conversion ratio (FCR). The research was conducted at the Kupang Livestock Training Center from April to May 2026 using a Completely Randomized Design (CRD) consisting of four treatments: P0 (100% basal feed), P1 (70% basal feed + 20% fermented coconut meal), P2 (75% basal feed + 25% fermented coconut meal), and P3 (80% basal feed + 30% fermented coconut meal). The results showed that fermented coconut meal supplementation improved the performance of Boerka goats. The highest ADG was obtained in treatment P3 at 311 g/head/day, while the lowest was recorded in P0 at 236 g/head/day. The highest feed intake was observed in P3 at 16.80 kg. The best feed conversion ratio was achieved in P1 with a value of 1.59. It can be concluded that fermented coconut meal has the potential to improve the growth performance of Boerka goats.